Empowering Communities through Non-Formal Education: A Case Study in Rural India - Archita Barigai; Lasya Heravdakar (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study investigate Empowering Communities through Non-Formal Education in rural india. The results of the research shows that alternative forms of education can greatly benefit local communities and promote individual agency. Those who took part said they learned something new, gained self-assurance and a sense of agency, grew closer to others, felt healthier and happier, and became more active in their communities.